Batch Arrival Queueing Model with Unreliable Server - Seenivasan, M.; S.Subasri, K. (International Journal of Engineering and Technology, 2018)
The unreliable server with provision of temporary server in the context of application has been investigated. A temporary server is installed when the primary server is over loaded i.e., a ï¬xed queue length of K-policy customers including the customer with the primary server has been build up. The primary server may breakdown while rendering service to the customers; it is sent for the repair. This type of queuing system has been investigated using Matrix Geometric Method to obtain the probabilities of the system steady state.AMS subject classiï¬cation numberâ€” 60K25, 60K30 and 90B22.Â Â